Forensic clinical anatomy of the spleen in medical malpractice. (November 2019) - Porzionato, Andrea; Macchi, Veronica; De Caro, Raffaele
Highlights: Some spleen anatomical variations/modifications may increase surgical risk. A Forensic Clinical Anatomy view invests their implications in Medical Liability. Main potential errors include misdiagnosis, unnecessary surgery, iatrogenic lesions. Variations include lobulation, accessory or wandering spleen, gonadal/pancreatic fusions. Main surgery- and trauma-induced modifications are adhesions and splenosis.